(untitled) (International Journal of Studies in Nursing, 2021)
Purpose: The study explores the description of nurses serving with the US Army and the American Red Cross during World War I as described in a collection of sheet music. The purpose was to identify themes within the lyrics which describe how the nurse was viewed at the time. Background: Analyzing the description of nurses who served during World War I allows the present-day reader insight into how they were perceived by the soldiers they cared for and the public. The contrast between the two types of songs; those written from the point of view of the soldiers and songs written from the point of view of the public, provides an insight into the depiction of the nurses. Method: Thematic analysis was used to review a collection of songs (N=29) for themes and examples of how nurses were described in the music lyrics of World War I music. Library of Congress music archives is the repository of the music reviewed. Findings and conclusions: The song lyrics from the soldiers’ point of view describe these women as beautiful, selfless angels, and much like their mothers back home. The lyrics from the public’s point of view describe the nurses as one who does her part for the war effort, one who doesn’t get enough praise, and a woman of courage. Many songs ask God to save the nurse. Looking back 100 years later, it is interesting to see how the nurse was a revered member of the US war effort during World War I.